A Large Ascending Aortic Aneurysm Secondary to Idiopathic Necrotizing Aortitis—A Rare but Important Cause of Thoracic Aortic Disease - Smeeton, Benjamin; Mustaev, Muslim; Sabetai, Michael (AORTA, 2019)
Idiopathic necrotizing aortitis is characterized by lymphoplasmacytic or giant cell-associated inflammation of the aorta, with no specific identifiable cause. We present the case of a 79-year-old man who sought medical attention from his primary care physician because of worsening shortness of breath. The patient underwent an elective ascending aorta, hemiarch, and aortic valve replacement. Histological examination of the aortic specimen demonstrated an unusually thin aorta with features consistent with necrotizing aortitis with giant cell infiltration.
Keywords: idiopathic necrotizing aortitis; aortic aneurysms; ascending aorta hemiarch replacement surgery; aortic valve replacement surgery